Postmenopausal Osteoporosis Is Associated with Serum Chemerin and Irisin but Not with Apolipoprotein M Levels - Engin-Üstün, Yaprak (J Menopausal Med, 2016)
OBJECTIVES: The objective of this study was to describe the levels of chemerin, irisin and apolipoprotein M (apoM) in women with postmenopausal osteoporosis. METHODS: The study included 88 women with postmenopausal osteoporosis. Based on World Health Organization criteria, women with a T-score of ≤ –2.5 were defined as osteoporotic. In this case-control study, postmenopausal women with T-score > –1 were selected as controls (n = 88) and case-matched in a 1:1 ratio based on age (within 2 years) and body mass index (BMI) (within 1.0 kg/m(2)). ApoM, irisin and chemerin levels were determined by a commercially available enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: There were no significant differences in age, BMI, parity, cholesterol and apoM levels between the two groups. C-reactive protein levels were significantly increased in women with osteoporosis. Serum chemerin levels (240.1 ± 46.1 vs. 261.5 ± 50.8 ng/mL) were significantly lower in the women with osteoporosis, as compared to the controls (P = 0.004). Serum irisin levels were also decreased in women with osteoporosis (0.7 ± 0.2 vs. 0.8 ± 0.2 ng/mL; P = 0.007). CONCLUSION: In the present study, osteoporosis was associated with decreased levels of circulating chemerin and irisin. These findings suggested that adipokines might play a role in the pathogenesis of osteoporosis.